Plasma Oxidized Albumin in Acute Ischemic Stroke Is Associated With Better Outcomes - Rael, Leonard T.; Leonard, Jan; Salottolo, Kristin; Bar-Or, Raphael; Bartt, Russell E.; Wagner, Jeffrey C.; Bar-Or, David (Frontiers in Neurology, 2019)
Introduction: Plasma oxidized human serum albumin (OxHSA) is evidence of an active antioxidant mechanism as measured by oxidized species of HSA. CXCL-10 is a pro-inflammatory chemokine associated with ischemic conditions. Accordingly, we examined the relationship of admission OxHSA and CXCL-10 with discharge mRS in acute ischemic stroke (AIS). Methods: Plasma samples and clinical data were collected prospectively at a Comprehensive Stroke Center. Admission biomarkers of oxidative stress, CXCL-10 and %OxHSA, were measured. We examined if CXCL-10 or %OxHSA correlated with age, admission NIHSS score, and discharge mRS score using Spearman's Rank correlation. Logistic regression was performed to identify independent predictors of a favorable discharge mRS (≤2). Results: In 106 consecutive AIS patients, the median age was 73 (IQR 61–84), 47% were male, and the median admission NIHSS score was 11 (IQR 5–19). %OxHSA and CXCL-10 were significantly correlated (r = 0.23, p = 0.02). Both biomarkers were significantly correlated with age: %OxHSA (r = 0.44, p < 0.001) and CXCL-10 (r = 0.32, p = 0.001). Neither biomarker was correlated with admission NIHSS. There was a borderline significant correlation with discharge mRS and %OxHSA (r = −0.17, p = 0.08), where higher %OxHSA correlated with lower discharge mRS scores. For every 1% increase in %OxHSA, the odds of a favorable discharge mRS increased 11%. The odds of a favorable discharge mRS decreased 18% for every 1-point increase in the initial NIHSS. Conclusions: OxHSA, the result of an oxidative environment and evidence of the strong antioxidant buffering capacity of HSA, correlated with CXCL-10 and discharge mRS, implying that strong antioxidant activity of albumin may confer better outcomes.